(untitled) (FUDMA JOURNAL OF SCIENCES, 2023)
The dependability of mobile robot towards the accomplishment of insistent tasks such as surveillance, continue to promote it real-world application. Propulsion of mobile robot can be legged or wheeled. However, the wheeled propelled mobile robot has been said to be the most applied category of mobile robots with mono-mode mobility control in literature. Therefore, the present work describes the methodology for the development of a dual mode mobility control for mobile robot. The research object is a differential drive wheeled mobile robot with night vision camera for remote surveillance. To validate the feasibility of the proposed mode of mobility experiment was conducted with comparison to mono-mode mobility control. Experimental result shows that the drawback with mono-mode platforms such as Wi-Fi, Internet, Bluetooth, Voice recognition and ZigBee as presented in literature is eliminated. In future, the incorporation of path planning competence will be given consideration for robot performance and application improvement